INTERNATIONAL TRANSIT TRADE AS AN IMPORTANT FACTOR OF INTERCONFESSIONAL AND INTER-NATIONAL TOLERANCE IN THE MEDIEVAL DERBENT - Inozemceva, E I (History, Archeology and Ethnography of the Caucasus, 2015)
Basing onthe data of archival documents and literary sources and taking into account the achievements of national historiography,the author of the article reveals the special role and importance of large-scale international transit trade in medieval Derbentas a powerful factor of peace,dialogueculture, civilized communication, and respect for the customs and beliefs of trading partners. In the context of the historical development of Caspian merchant shipping in the 10th–18th centuries the author shows to what extent the various peoples gravitating towards the Caspian Sea took part in it. The article covers the role of Derbent in the ‘silk transit’ from Persia through Dagestan and the Russian state to Western Europe via the Great Volga-Caspian Route and shows the significance of this fact for the economic development of the peoples, especially for Dagestan people. The author emphasizes the special interest of Russian government in intercontinental transit, highlights the place of Dagestan and in particular of Derbent in the Caucasian economic policy of Russia.